MANAJEMEN PENGEMBANGAN KURIKULUM SEKOLAH BERBASIS AGAMA - Imron, Indah Puspitasari, Sutriani, Baraz Yoechva Alfaiz,Mohammad Yasin Al (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2024)
Abstract: The educational curriculum in Islamic boarding schools has an important role in developing an education system based on local wisdom. The development of the curriculum in Islamic boarding schools is expected to provide a distinctive feature in the dynamics of national education. This qualitative research uses a narrative literature review approach by referring to various manuscripts that discuss education, especially Islamic boarding schools. Data was collected through document review and confirmation through random observation in several sample Islamic boarding schools. The results show that the curriculum development in sekolah still retains its characteristics, although the classical education model is difficult not to be influenced by modern education. Humanistic education is also applied to help students explore their potential naturally. Curriculum reconstruction is needed so that social learning goals can be achieved, so that students are ready to face life in society. The principle of cooperation and mutual respect is emphasized in the learning process to create a conducive atmosphere.Keywords: Management, Curriculum Development, SchoolAbstrak Kurikulum pendidikan di sekolah memiliki peran penting dalam mengembangkan sistem pendidikan berbasis kearifan lokal. Pengembangan kurikulum di sekolah diharapkan memberikan ciri khas dalam dinamika pendidikan nasional. Penelitian kualitatif ini menggunakan pendekatan narrative literature review dengan mengacu pada berbagai manuskrip yang membahas pendidikan, terutama sekolah. Data dikumpulkan melalui telaah dokumen dan konfirmasi melalui observasi acak di beberapa sekolah sampel. Hasil penelitian menunjukkan bahwa pengembangan kurikulum di sekolah tetap mempertahankan karakteristiknya, meskipun model pendidikan klasik sulit untuk tidak terpengaruh oleh pendidikan modern. Pendidikan humanistik juga diterapkan untuk membantu santri menggali potensi diri secara alami. Rekonstruksi kurikulum diperlukan agar tujuan pembelajaran yang bersifat sosial dapat tercapai, sehingga santri siap menghadapi kehidupan di masyarakat. Prinsip kerjasama dan saling menghargai ditekankan dalam proses pembelajaran untuk menciptakan suasana yang kondusif.Kata Kunci: Manajemen, Pengembangan Kurikulum, Sekolah